Optimasi Kemampuan Membaca Kritis Mahasiswa melalui Pembelajaran Metaphorming Berbasis Kearifan Lokal dan Aplikasi Flip - Afrodita, Meli; Wulandari, Catur; Ismawati, Dwi; Sari, Dwi Lyna (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to improve students' critical reading skills through the application of local wisdom-based metaphorming methods and the use of flip applications in the Reading Skills course. This study used a classroom action research design which was carried out in two cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. Data were collected through observation, test, and questionnaire which were analyzed descriptively qualitative and quantitative. The results showed that the application of the local wisdom-based metaphorming method, which used Bengkulu folklore as teaching material, was effective in improving students' critical reading skills. In addition, the use of the flip application as an interactive learning media contributed positively to the increase in student involvement in the learning process. Students' learning outcomes showed a significant improvement from cycle I to cycle II, with the percentage of students who reached the minimum completion score increasing from 21.62% in cycle I to 81.08% in cycle II. Thus, this learning method proved effective in improving students' critical reading skills and learning motivation. This study recommends that similar methods be applied to other courses to improve students' critical thinking skills and creativity.